Analysis of the Import and Export to Measure Revenue Customs Authority (AA) Customs in Dili, Timor-Leste - Maia, Fonseca De Jesus; Nunes, Esperança Da Costa (Sinergi International Journal of Accounting and Taxation, 2024)
The research was conducted at the Customs Authority. The objective of this research is to see about the analysis of imports and exports to measure tax revenue from the period 2019-2022. In this research, the contribution of import and export taxes to tax revenues is used. The results of the research identified that the analysis of the tax contribution of the Import Tax Contribution of Rice and Coffee 2019-2020. In this research, the type of research used is quantitative research which is a type of research based on numbers, starting from data collection, interpretation of data and looking at the results. Starting from the results of calculation and discussion of the contribution of import tax of rice and coffee to the country's income. The contribution of the mortgage rate in the four years from 2019 to 2022 received financial fluctuations. The average financial value of the tax contribution amounts to 5.81%. In 2019, financial value was 4.49% because taxpayers tax contribution with minimum because they get low profit, in 2020 financial value with 11.67% taxpayers contribute maximum tax, in 2021 financial value with 4.32 %, and in 2022 the financial value decreased by 1.10% because taxpayers receive profits according to the taxpayer's income so the tax contribution is low, taxpayers contribute taxes according to their profits.